ANALYSIS WATER AVAILABILITY AND WATER BALANCE IN IRRIGATION AREAS RINTAU, DISTRICT SEKAYAM - Yuanita, Ezzy; Kartini, Kartini; Soeryamassoeka, S B (Jurnal Teknik Sipil, 2023)
Indonesia's population is increasing yearly, which has led to a decrease in water supply in several places, including the Sekayam Sub-district, Sanggau District, and West Kalimantan Province. The Rintau irrigation area (D.I.Rintau), located in Sekayam Sub-district, has a potential size of 528.52 Ha. However, due to land conversion for communities and plantations, its functional area is only 224.94 Ha. In addition to reducing the amount of available land, Rintau irrigation has issues with crops and plants that do not match the water supply of the irrigation system.This research aims to get the most suitable cropping pattern in Rintau irrigation related to water availability. The analysis includes water availability with the Mock Model, NFR analysis, water demand in the retrieval building (DR), and water balance analysis.  According to the analysis results, the maximum mainstay discharge of raw water sources used by Rintau irrigation is 707.512 l/sec, the minimum mainstay discharge is 114.200 l/sec, and the average mainstay discharge is 402.619 l/sec. The most suitable cropping pattern used in Rintau Irrigation is the rice-paddy-cucumber cropping pattern, with a maximum NFR value of 8.146 mm/day or 0.943 lt/sec, and the beginning of the first planting period in the first half of August and starting planting 2 in the first half of December. Thus, the Rice-Paddy-Cucumber cropping pattern can be applied to Rintau irrigation to increase food production. Its management must be pursued using appropriate cropping technology.